Professional service firms - Greenwood, Royston; Suddaby, Roy (Research in the sociology of organizations, 2006)
This volume includes studies of organizations that deliver professional services, including accounting, law, and management consulting firms. These organizations are of importance for several reasons: they underpin the modern economy, enabling economic exchange; they constitute the 'intellect industry', developing and disseminating new ideas; and, they are exemplars of knowledge-intensive organizations. Contributors include researchers from North America and Europe. This book series is available electronically online.